2009
DOI: 10.1098/rsbl.2009.0334
|View full text |Cite
|
Sign up to set email alerts
|

Environmentally induced responses co-opted for reproductive altruism

Abstract: Reproductive altruism is an extreme form of altruism best typified by sterile castes in social insects and somatic cells in multicellular organisms. Although reproductive altruism is central to the evolution of multicellularity and eusociality, the mechanistic basis for the evolution of this behaviour is yet to be deciphered. Here, we report that the gene responsible for the permanent suppression of reproduction in the somatic cells of the multicellular green alga, Volvox carteri , evol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
78
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(86 citation statements)
references
References 20 publications
8
78
0
Order By: Relevance
“…Although C. reinhardtii lacks an exact regA ortholog, phylogenetic analysis of the VARL gene family suggests that this is due to gene loss in the C. reinhardtii lineage rather than a gene duplication in the V. carteri lineage (Duncan et al, 2007). The most closely related C. reinhardtii regA homolog is induced under nutrient and light-deprivation, leading to the suggestion that the somatic differentiation function of regA was co-opted from an environmental acclimation function in the unicellular ancestor of V. carteri (Nedelcu & Michod, 2006;Nedelcu, 2009). …”
Section: B Ecology and Molecular Evolution Of Oceanic Picoplanktonicmentioning
confidence: 99%
“…Although C. reinhardtii lacks an exact regA ortholog, phylogenetic analysis of the VARL gene family suggests that this is due to gene loss in the C. reinhardtii lineage rather than a gene duplication in the V. carteri lineage (Duncan et al, 2007). The most closely related C. reinhardtii regA homolog is induced under nutrient and light-deprivation, leading to the suggestion that the somatic differentiation function of regA was co-opted from an environmental acclimation function in the unicellular ancestor of V. carteri (Nedelcu & Michod, 2006;Nedelcu, 2009). …”
Section: B Ecology and Molecular Evolution Of Oceanic Picoplanktonicmentioning
confidence: 99%
“…In addition, the mechanistic basis for the evolution of somatic cell differentiation (at least in V. carteri) can also be traced back to the ability of single-celled volvocine ancestors to temporarily repress their reproduction to increase survival, as part of their general photo-acclimation response to limiting or stressful conditions Nedelcu 2009b). However, the very same factors that allowed some lineages in this group to achieve high levels of complexity may have affected how complex they could become.…”
Section: Independent Increases In Complexitymentioning
confidence: 98%
“…21) and the green alga Volvox carteri (Nedelcu 2009b). Likewise, genes involved in moss development have been found in the closest unicellular relatives of land plants .…”
Section: Proximate Causesmentioning
confidence: 98%
See 1 more Smart Citation
“…Sequencing of gonidial-specific genes showed that 15 of the 19 encoded proteins were predicted to be involved in photosynthesis-related functions, suggesting that photosynthetic activity may be suppressed in somatic cells (Meissner et al, 1999). This finding has led to the idea that suppression of photosynthesis may be the primary mechanism for inducing a senescent fate in somatic cells, such that somatic cells are unable to grow sufficiently large or rapidly enough to reproduce (Kirk, 2001; Meissner et al, 1999; Michod, 2007; Nedelcu and Michod, 2004; Nedelcu, 2009). It should be noted, however, that information about comparative rates and productivity of photosynthesis in somatic versus gonidial cells is lacking, and that somatic cells have been shown to actively fix CO 2 (Pommerville and Kochert, 1982) and must also consume energy to maintain basal metabolism, flagellar motility and biosynthesis and secretion of ECM.…”
Section: Cell-type Differentiationmentioning
confidence: 99%